Contribution to the knowledge of genus Clanoptilus Motschulsky, 1854 in the Eastern Mediterranean region (Coleoptera: Melyridae, Malachiinae) - Franzini, Gabriele (Fragmenta entomologica, 2024)
This paper deals with two species of the genus Clanoptilus Motschulsky, 1854. A new one is described from Aegean region of Turkey; one from Azerbaijan is resurrected from synonymy and redescribed, and a neotype is proposed.